Transworlding: navigating spaces and negotiating the self in online schooling - Jill Koyama (Universidade Federal do Rio Grande do Sul, 2020)
Drawing on data from a 42-month ethnography of refugee networks in Arizona, I explore refugee youth forging hybrid identities and spaces in US educational contexts. Utilizing the notion of space-making (Das Gupta, 2006), I demonstrate how they simultaneously stream webcam video from a refugee camp or music from their home countries while completing lessons in an online credit recovery program or high school course. They engage in what I refer to as transworlding, or the practice of mediating emergent identities and navigating figured worlds (Holland; Lachicotte; Skinner; Cain, 1998) of refugee learning while challenging normative and marginalizing educational practices.